A Nutritional Conditional Lethal Mutant Due to Pyridoxine 5'-Phosphate Oxidase Deficiency in Drosophila melanogaster. - Chi, W.; Zhang, L.; Du, W.; Zhuang, X. (G3 : genes - genomes - genetics, 2014)
The concept of auxotrophic complementation has been proposed as an approach to identify genes in essential metabolic pathways in Drosophila melanogaster. However, it has achieved limited success to date, possibly due to the low probability of finding mutations fit with the chemically defined profile. Instead of using the chemically defined culture media lacking specific nutrients, we used bare minimum culture medium, i.e., 4% sucrose, for adult Drosophila. We identified a nutritional conditional lethal mutant and localized a c.95C > A mutation in the Drosophila pyridoxine 5'-phosphate oxidase gene [dPNPO or sugarlethal (sgll)] using meiotic recombination mapping, deficiency mapping, and whole genome sequencing. PNPO converts dietary vitamin B6 such as pyridoxine to its active form pyridoxal 5'-phosphate (PLP). The missense mutation (sgll(95)) results in the substitution of alanine to aspartate (p.Ala32Asp). The sgll(95) flies survive well on complete medium but all die within 6 d on 4% sucrose only diet, which can be rescued by pyridoxine or PLP supplement, suggesting that the mutation does not cause the complete loss of PNPO activity. The sgll knockdown further confirms its function as the Drosophila PNPO. Because better tools for positional cloning and cheaper whole genome sequencing have made the identification of point mutations much easier than before, alleviating the necessity to pinpoint specific metabolic pathways before gene identification, we propose that nutritional conditional screens based on bare minimum growth media like ours represent promising approaches for discovering important genes and mutations in metabolic pathways, thereby accelerating the establishment of in vivo models that recapitulate human metabolic diseases.